2023
DOI: 10.1001/jamanetworkopen.2023.18320
|View full text |Cite
|
Sign up to set email alerts
|

Blood Donors' Preferences Toward Incentives for Donation in China

Yu Wang,
Peicong Zhai,
Shan Jiang
et al.

Abstract: ImportanceBlood donation is critical for health care systems, but donor retention remains challenging. Understanding donors’ preferences can inform incentive design and improve retention rates.ObjectiveTo identify donor preferences for incentive attributes and their relative importance in promoting blood donation among Chinese donors in Shandong.Design, Setting, and ParticipantsThis survey study fielded a discrete choice experiment (DCE) with a dual response design among blood donors, analyzing the responses u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Second, similar to previous research among active donors in China [12], findings from the present study indicated that small token gifts (e.g., mugs) were important to experienced and inexperienced donors alike. Small token gifts such as mugs may have limited monetary value but may effectively demonstrate gratitude to the donor.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Second, similar to previous research among active donors in China [12], findings from the present study indicated that small token gifts (e.g., mugs) were important to experienced and inexperienced donors alike. Small token gifts such as mugs may have limited monetary value but may effectively demonstrate gratitude to the donor.…”
Section: Discussionsupporting
confidence: 88%
“…The total volume of blood donated in 2022 was 27.6 million units, with an average annual growth rate of 14.5% [8, 9], and the number of blood donors in 2022 exceeded 16 million, with an average annual growth rate of the number of blood donors of 16.3 percent [8, 9]. To date, approximately 453 blood stations have been constructed nationwide [9], and the level of blood security has greatly improved [10–16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Original Investigation titled “Blood Donors’ Preferences Toward Incentives for Donation in China,” 1 published June 14, 2023, and in the Invited Commentary titled “Genome Sequencing for Newborn Screening—An Effective Approach for Tackling Rare Diseases,” 2 published September 1, 2023, there were errors in the bylines. Shan Jiang’s degree should have been listed as an MSc.…”
mentioning
confidence: 99%